Generational differences in dietary pattern among Brazilian adults born between 1934 and 1975: a latent class analysis - Bezerra, Ilana Nogueira (2018)
Maria da Conceição Chagas de Almeida. Fundação Oswaldo Cruz. Instituto Gonçalo Moniz. Salvador, BA, Brasil. “Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta à informação no documento”.